Inherent Safety Characteristics of Lead Bismuth Eutectic-Cooled Accelerator Driven Subcritical Systems - Luo, Run; Revankar, Shripad T.; Zhang, De; Zhao, Fuyu (Frontiers in Energy Research, 2022)
Accelerator driven subcritical system (ADS) is a new nuclear energy system which could not only produce clean energy but also incinerate nuclear waste. In this paper, inherent safety analysis of an ADS is performed with neutronics and thermal-hydraulics coupled code named ARTAP. Five typical accidents are carried out, including the cases of proton beam interruption, transient overpower, reactivity insertion, loss of flow, and loss of heat sink. The transient simulations are performed in the average channel and the hottest channel of the fuel pin in the ADS core. The simulation results for beam interruption shows that the highest temperature of pellet is in the middle of the fuel element in the average channel, while the peak temperature of cladding is in the top of the fuel element. After the beam is interrupted for 20s, the maximum temperature drops of the fuel center, the cladding inner surface and the outlet coolant in the hottest channel are 644.46K, 162.27K and 136.42K respectively. For transient overpower accident with the increase of beam intensity, the maximum temperature of the fuel and the cladding are below the safety limit. Concerning the reactivity insertion accident, it is found that the ADS has good inherent safety and its margin of criticality safety is large. The calculation results for loss of flow show that the power drop is small due to low sensitivity of the subcritical core to negative reactivity feedback, and the maximum temperature of the cladding reaches 1726K, which means the fuel element would rupture. However, the power and the temperatures of fuel, cladding and coolant could decrease quickly to the safety level after the proton accelerator is cutted off under loss of flow accident. The results also show that the peak temperature of the cladding is lower than the safety limit under loss of heat sink accident. The present simulation results reveal that the ADS has a remarkable advantage against severe accidents. It also implies that its inherent safety characterizes could ensure reactor shutdown by cutting off the proton beam after accidents occur.